2018
DOI: 10.1186/s12870-018-1472-5
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid reverses pollen abortion of rice caused by heat stress

Abstract: BackgroundExtremely high temperatures are becoming an increasingly severe threat to crop yields. It is well documented that salicylic acid (SA) can enhance the stress tolerance of plants; however, its effect on the reproductive organs of rice plants has not been described before. To investigate the mechanism underlying the SA-mediated alleviation of the heat stress damage to rice pollen viability, a susceptible cultivar (Changyou1) was treated with SA at the pollen mother cell (PMC) meiosis stage and then subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 79 publications
(88 reference statements)
1
38
0
Order By: Relevance
“…Although, ROS scavenging is key to ensure that heat stress does not damage the sensitive reproductive tissue, ROS‐dependent programmed cell death is essential for successful fertilisation (Suzuki & Katano, ). Some thermo‐protectants including primary metabolites and phyto‐hormones such as ‐aminobutyric acid (mungbean ( Vigna radiate ), Priya et al , ); salicylic acid (rice, Feng et al , ); flavonols (tomato, Muhlemann et al , ); auxin (rice, Zhang et al , ); and ethylene (tomato, Jegadeesan et al , ) continue to be effective in alleviating heat stress damage in pollen. Although, there are no studies in this direction involving pistils per se , a plausible hypothesis would be that the above‐mentioned compounds will have a similar alleviation potential in pistils exposed to heat stress (Box 2).…”
Section: Male and Female Reproductive Organ Viabilitymentioning
confidence: 99%
“…Although, ROS scavenging is key to ensure that heat stress does not damage the sensitive reproductive tissue, ROS‐dependent programmed cell death is essential for successful fertilisation (Suzuki & Katano, ). Some thermo‐protectants including primary metabolites and phyto‐hormones such as ‐aminobutyric acid (mungbean ( Vigna radiate ), Priya et al , ); salicylic acid (rice, Feng et al , ); flavonols (tomato, Muhlemann et al , ); auxin (rice, Zhang et al , ); and ethylene (tomato, Jegadeesan et al , ) continue to be effective in alleviating heat stress damage in pollen. Although, there are no studies in this direction involving pistils per se , a plausible hypothesis would be that the above‐mentioned compounds will have a similar alleviation potential in pistils exposed to heat stress (Box 2).…”
Section: Male and Female Reproductive Organ Viabilitymentioning
confidence: 99%
“…Heat stress is one of the most important abiotic stresses and causes irreversible damage to rice plants (Jajoo & Allakhverdiev, ; Kumazaki & Suzuki, ), resulting in the inactivation of thermolabile proteins, ROS accumulation, and ultimately PCD (Feng et al, ; Singh et al, ). If such stress occurs at the reproductive stage, grain yield is significantly decreased (Feng et al, ; Fu et al, ; Zhang et al, ). At anthesis, the pollen germination and pollen tube elongation are inhibited by heat stress, which was mainly inferred due to an energy imbalance (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…WRKY genes encode TFs that play important roles in abiotic stress responses , especially to abscisic acid (ABA) (Zhen et al 2005). In this study, six DEGs were WRKY TFs, namely, BGIOSGA003134, BGIOSGA017063, BGIOSGA029574, BGIOSGA005924, BGIOSGA024948, and BGIOSGA033505, which might promote young panicle development associated with sucrose consumption mediated by ABA under high temperature (Feng et al 2018). However, few studies have reported the relationship between the WRKY family and heat resistance, which should be further studied.…”
Section: Discussionmentioning
confidence: 79%